Thanatophoric dysplasia: a case report at Federal Medical Centre Yenagoa, Bayelsa state Nigeria - Onotume, Okemena O.; Idholo, Urire; Tunde-Oremodu, Immaculata I.; Okosun, Ofure; Adeyemi, Oyedeji O.; Kunle-Olowu, Onyaye (International Journal of Contemporary Pediatrics, 2022)
Thanatophoric dysplasia is a rare congenital severe skeletal disorder previously considered lethal but some survivals beyond the neonatal period have been reported due to extensive medical interventions. There have been a few studies on thanatophoric dysplasia in Africa and specifically in Nigeria hence this case report of an 8-day old female who was born with clinical features that were consistent with thanatophoric dysplasia creating awareness in this region. An eight-day old female term neonate who was seen in the special care baby unit with respiratory distress and limb abnormalities from birth. Two obstetric ultrasound scans had revealed a fetus with severe limb deformity. At presentation, she was in respiratory distress, with dysmorphic features, small chest wall with chest hypertelorism. The limbs were short having marks of amniotic bands with lymphoedema affecting both lower limbs. There were no palmar creases. Skeletal survey done revealed marked hypoplasia of the chest cavity, and widening of both proximal and distal epiphyses of all long bones showing telephone receiving appearance. Echocardiography and abdominal ultrasound scans were normal. It was documented that thanatophoric dysplasia was inherited in an autosomal dominant fashion however sporadic mutations do occur as seen in this patient who had no family history. Facility for genetic testing to analyse the fibroblast growth factor receptor (FGFR3) for typing and determining possible mutations was not available to confirm the diagnosis however, her clinical features and radiological findings were suggestive of thanotophoric dysplasia type 1.